Small-Scale Flat Plate Collectors for Solar Thermal Scavenging in Low Conductivity Environments - Emmanuel Ogbonnaya; Leland Weiss (International Journal of Photoenergy)
There is great opportunity to develop power supplies for autonomous application on the small scale. For example, remote environmental sensors may be powered through the harvesting of ambient thermal energy and heating of a thermoelectric generator. This work investigates a small-scale (centimeters) solar thermal collector designed for this application. The absorber is coated with a unique selective coating and then studied in a low pressure environment to increase performance. A numerical model that is used to predict the performance of the collector plate is developed. This is validated based on benchtop testing of a fabricated collector plate in a low-pressure enclosure. Model results indicate that simulated solar input of about 800 W/m2 results in a collector plate temperature of 298 K in ambient conditions and up to 388 K in vacuum. The model also predicts the various losses in W/m2 K from the plate to the surroundings. Plate temperature is validated through the experimental work showing that the model is useful to the future design of these small-scale solar thermal energy collectors.